Low-dose lenalidomide and dexamethasone combination treatment in elderly patients with relapsed and refractory multiple myeloma. Issue 2 (7th February 2017) - Wang, Chunling; He, Zhengmei; Shi, Yuye; Zhang, Lijuan; Chen, Yue; Chen, Zhi; Yu, Liang
ABSTRACT: Objective : This study investigated the efficacy and safety of low-dose lenalidomide combined with dexamethasone in elderly patients with relapsed and refractory multiple myeloma (MM). Methods : Thirty-two elderly patients with refractory and recurrent MM (median age: 64 years) were treated with low-dose lenalidomide (LD-R) combined with dexamethasone (D). LD-R (10 mg/d) was administered orally for 21 days and D (40 mg/d) was administered twice a day on days 1–4, 9–12, and 17–20. The treatment lasted 2–8 28-day cycles. Results : After two cycles, the complete, very good partial, and partial remission rates were 12.5% (4/32), 25.0% (8/32), and 34.4% (11/32), respectively. The overall response rate was 71.9% (23/32). After a 24-month follow-up, 23 patients responded to therapy, three were in complete remission, four were stable, and 16 exhibited disease progression. In addition, median time-to-progression was 13 months. Observed side effects were hypodynamia, gastrointestinal reaction, peripheral neuritis, and mild hypocytosis. Conclusion : Low-dose lenalidomide in combination with dexamethasone is an effective and safe treatment for relapsed and refractory MM in elderly patients.